THE EFFECT OF STATOR WINDING RESISTANCE REDUCTION ON THE PERFORMANCE OF A THREE-PHASE INDUCTION MOTOR - Giovanni Dimas Prenata; Labib Ubaidillah Iskhan; Reza Sarwo Widagdo (TESLA: Jurnal Teknik Elektro, 2026)
This study experimentally investigates the impact of stator winding resistance degradation on the electrical, mechanical, and thermal performance of a three-phase induction motor under four resistance levels (6.8 Ω, 5.7 Ω, 3.9 Ω, and 3.5 Ω) and five loading conditions (no-load, generator load, and one to three lamp loads) using measurements of voltage, current, power factor, rotational speed, torque, output power, temperature, and efficiency. The results show that decreasing stator winding resistance consistently increases current and temperature while reducing power factor, speed, and efficiency under all loading conditions; under generator load, reducing the resistance from 6.8 Ω to 3.5 Ω decreases the speed from 1447.6 rpm to 1364.6 rpm, increases the current from 2.31 A to 3.40 A, and reduces the efficiency from 89.68% to 75.16%, with the winding temperature approaching 50 °C. These findings demonstrate that stator winding resistance degradation is a direct indicator of performance deterioration and reliability loss in induction motors, and that multi-parameter measurements across different load levels provide a strong experimental basis for stator condition monitoring and predictive maintenance Abstrak Penelitian ini menganalisis secara eksperimental pengaruh penurunan resistansi belitan stator terhadap kinerja listrik, mekanik, dan termal motor induksi tiga fasa pada empat kondisi resistansi (6,8 Ω, 5,7 Ω, 3,9 Ω, dan 3,5 Ω) dan lima tingkat pembebanan (tanpa beban, generator, serta satu hingga tiga lampu) dengan pengukuran tegangan, arus, faktor daya, kecepatan, torsi, daya, suhu, dan efisiensi. Hasil menunjukkan bahwa penurunan resistansi belitan secara konsisten meningkatkan arus dan suhu, menurunkan faktor daya, kecepatan, dan efisiensi pada semua kondisi beban; pada beban generator, penurunan resistansi dari 6,8 Ω menjadi 3,5 Ω menurunkan kecepatan dari 1447,6 rpm menjadi 1364,6 rpm, meningkatkan arus dari 2,31 A menjadi 3,40 A, dan menurunkan efisiensi dari 89,68% menjadi 75,16% dengan suhu belitan mendekati 50 °C. Temuan ini menunjukkan bahwa degradasi resistansi belitan stator merupakan indikator langsung penurunan kinerja dan keandalan motor induksi, sehingga pengukuran multi-parameter pada berbagai tingkat beban memberikan dasar eksperimental yang kuat untuk diagnosis kondisi belitan dan pemeliharaan prediktif